Thermal barrier coating and preparation method thereof

By using materials such as silicone resin, ceramic precursor, hollow microbeads and chopped fibers in the thermal barrier coating, combined with surface modifiers and components such as lanthanum oxide and chromium oxide, the thermal barrier coating is solved at high temperatures. The stability and performance issues in the environment enable high-performance thermal barrier coatings.

CN119432227APending Publication Date: 2025-02-14AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411672356.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing thermal barrier coatings have problems of stability and performance degradation in high temperature environments, especially in terms of poor compatibility, uneven dispersion and high thermal conductivity of different types of fillers.

Method used

By fully mixing the silicone resin with ceramic precursors, hollow microbeads and chopped fibers, and adding surface modifiers and lanthanum oxide and chromium oxide to form a high-performance thermal barrier coating. The method includes spraying or brushing the final D onto the material to be protected, and after the solvent evaporates and drys, forming a erosion-resistant thermal barrier coating.

Benefits of technology

It realizes the heat resistance, low thermal conductivity, erosion resistance, high surface hardness and high emissivity of thermal barrier coatings, and is suitable for aircraft and missile applications in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005146175920000041
    Figure BDA0005146175920000041
  • Figure BDA0005146175920000051
    Figure BDA0005146175920000051
  • Figure BDA0005146175920000061
    Figure BDA0005146175920000061
Patent Text Reader

Abstract

The invention discloses a thermal barrier coating and a preparation method thereof, and belongs to the field of high polymer materials and heat-proof coatings. A component A is prepared from organic silicon resin and a ceramic precursor, a component B is prepared from hollow microspheres, chopped fibers and a surface modifier, the two components are mixed and then coated on a to-be-protected material, and the thermal barrier coating is obtained. A component C can be prepared from lanthanum oxide and chromium oxide crystals, and the three components are mixed and then coated on a to-be-protected material to obtain the thermal barrier coating with better performance. The thermal barrier coating prepared by the method has the advantages of heat resistance, low thermal conductivity, scouring resistance, high surface hardness, high emissivity and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials and heat-resistant coatings, and relates to a thermal barrier coating and a preparation method thereof. Background Art

[0002] When an aircraft flies in the atmosphere, high temperatures will be generated due to air flow friction, requiring effective heat protection and insulation measures. At present, the most commonly used of various types of thermal protection materials are ablative heat protection materials, which use the loss of the material itself to achieve heat dissipation, prevent heat conduction from entering the interior of the material, and achieve thermal protection for the aircraft. As a special type of ablative heat insulation material, thermal barrier coatings have important applications in aerospace. They have simple coating processes, are less affected by product structure, and have low costs and short coating cycles. They are widely used in heat protection of the outer surfaces of engines and aircraft cabins. As aircraft flight speeds increase and flight time increases, the aerodynamic heating environment faced by thermal protection materials becomes more severe, placing higher demands on the long-term service heat insulation of aircraft structures and the stable and reliable performance of coatings.

[0003] For ablative thermal insulation coatings, the type and content of the fillers used determine a series of physical and chemical properties of the coatings. In order to reduce the density and thermal conductivity of the coating, hollow microspheres, lightweight aerogels and other fillers are often used; in order to improve the integrity and mechanical properties of the coating, various fiber fillers are widely used. However, due to the differences in the materials and structures of different fillers, during the preparation of the coating, problems such as difficulty in dispersing different types of fillers, easy agglomeration, easy stratification and sedimentation, and poor compatibility are prone to occur, which is not conducive to the uniform mixing of the components and the stability of the coating, and the comprehensive properties of the coating, such as thermal conductivity and mechanical properties, are reduced. Therefore, improving the compatibility of different types of fillers with coatings and preparing uniformly dispersed ablative thermal insulation coatings with high mechanical properties are of great significance to the development of coating material technology. Summary of the invention

[0004] The object of the present invention is to provide a thermal barrier coating and a preparation method thereof, wherein the thermal barrier coating has the advantages of heat resistance, low thermal conductivity, erosion resistance, high surface hardness, high emissivity and the like.

[0005] The technical solution adopted by the present invention to achieve its purpose is as follows:

[0006] The present invention provides a method for preparing a thermal barrier coating, comprising the following steps:

[0007] Add 5 to 15 parts by weight of a ceramic precursor to 100 parts by weight of an organic silicone resin, and mix thoroughly to obtain component A;

[0008] 10 to 30 parts by weight of hollow microspheres and 10 to 30 parts by weight of chopped fibers are fully mixed and dispersed in solvent X, a surface modifier is added, and the mixture is uniformly mixed to form component B;

[0009] Mix component A and component B evenly to form final product D;

[0010] The final product D is sprayed or brushed on the material to be protected, and after the solvent evaporates and dries, an ablation-resistant thermal barrier coating is obtained.

[0011] Furthermore, the silicone resin includes but is not limited to one of trapezoidal polymethylsilsesquioxane, trapezoidal polyphenylsilsesquioxane, trimethylmethoxysilane, methyltrimethoxysilane, methylphenyl silicone resin, phenyltrimethoxysilane, ethyl orthosilicate, and propyl orthosilicate; preferably one of the phenyl-containing silicone resins, the phenyl group in the molecular chain can increase the decomposition temperature of the silicone resin and increase the proportion of residues (residual carbon rate) after thermal decomposition of the resin.

[0012] Furthermore, the hollow microspheres include but are not limited to glass microspheres, ceramic microspheres, or a mixture of the two, with a particle size of 50 to 100 um.

[0013] Furthermore, the chopped fibers include but are not limited to high-silica fibers (high-purity glass fibers with a silica content of 96% to 95%), glass fibers, quartz fibers, aramid fibers, and mixed fibers of one or more of aramid fibers, with a fiber length of 50 to 100 um; preferably, quartz fibers and Kevlar fibers are mixed in a 1:1 ratio to have both strength and toughness.

[0014] Further, the ceramic precursor includes but is not limited to one of zirconium boride, silicon carbide, boron nitride, silicon tetraboride, and silicon hexaboride, preferably zirconium boride.

[0015] Further, the surface modifier includes but is not limited to one of γ-aminopropyl triethoxysilane, γ-(methacryloxy)propyl trimethylsilane, γ-glycidyloxypropyl trimethoxysilane, vinyl triethoxysilane, and vinyl trimethoxysilane; preferably one of γ-aminopropyl triethoxysilane and γ-(methacryloxy)propyl trimethylsilane. The amount of the surface modifier added is 5% to 10% of the mass of the ceramic precursor.

[0016] Furthermore, the method further comprises the following steps: grinding and stirring 5 to 15 parts by mass of lanthanum oxide and 5 to 15 parts by mass of chromium oxide crystals in a ball mill, sintering the mixture at high temperature in a crucible, cooling the mixture to room temperature with the furnace, adding solvent Y and mixing the mixture evenly to form component C; and adding component C to the mixture of component A and component B to form a final product D.

[0017] Further, the solvent X and the solvent Y are the same or different, are miscible with each other, and can dissolve the silicone resin, the ceramic precursor, lanthanum oxide, and chromium oxide.

[0018] Furthermore, solvent X and solvent Y include but are not limited to one of ethanol, isopropanol, toluene, n-hexane, chloroform, tetrachloromethane, and bromate solution, preferably one of ethanol, n-hexane, and toluene.

[0019] The present invention also provides a thermal barrier coating, which is prepared by the above preparation method.

[0020] The present invention has achieved the following beneficial effects:

[0021] 1. The chromium oxide selected in the present invention has good spraying process performance, wide spraying process specification, and the coating is not easy to crack when it is locally overheated. The sprayed layer is very dense, has high hardness, high bonding strength with the substrate, and good anti-scouring performance.

[0022] 2. The lanthanum oxide and chromium oxide selected by the present invention have high temperature resistance and good thermal stability at high temperatures, which can further ensure the integrity of the coating at high temperatures; and the two have similar crystal structures, and can better synthesize a composite structure of a perovskite structure through a solid phase reaction, and this structure has good radiation performance. Lanthanum oxide and chromium oxide have similar crystal structures, and can better synthesize a composite structure of a perovskite structure through a solid phase reaction, and this structure has good radiation performance, which can improve the thermal protection effect (radiant heat) of the coating.

[0023] 3. The ceramic microbeads selected in the present invention not only have the characteristics of low density and low thermal conductivity, but also have electromagnetic effects, which can further enhance the emissivity of the coating.

[0024] 4. The present invention uses chopped fibers as reinforcement, which has a fiber reinforcement effect, enhances the mechanical properties and toughness of the coating, avoids cracking of the matrix after curing and ablation, and improves the mechanical properties and overall toughness of the coating.

[0025] 5. The solvent X and solvent Y selected in the present invention are mutually soluble and form a uniformly dispersed solution when mixed. After spraying, they can evaporate quickly at room temperature to achieve rapid drying of the coating.

[0026] 6. The thermal barrier coating prepared by the present invention has the advantages of heat resistance, low thermal conductivity, erosion resistance, high surface hardness, etc. It is suitable for the surface of metal substrates such as aluminum alloys and titanium alloys or carbon fiber composite materials or used in combination with other thermal protection materials. It is mainly used in missile cabins, engines, tail wings, cable covers, etc., and launch vehicles' end caps, heat shields and other working parts subject to high heat flux erosion. DETAILED DESCRIPTION

[0027] In order to make the various technical features and advantages or technical effects in the above technical solutions of the present invention more obvious and easy to understand, they are described in detail below in conjunction with embodiments.

[0028] Before listing the embodiments of the present invention, four comparative examples are first listed, in which coating products are prepared by using existing preparation methods, for comparison with the embodiments.

[0029] It should be noted that the operations of mixing, dispersing, spraying, brushing, drying, etc. mentioned in the present invention all adopt conventional technical means in the field. For the convenience of writing, specific condition parameters are no longer given. Those skilled in the art can implement them according to the common knowledge they have mastered. The reasonable changes in the condition parameters of these operations in the specific implementation can have a negligible effect on the final preparation result, which should be understandable to those skilled in the art.

[0030] Comparative Example 1:

[0031] 1. Take 100g of silicone resin, add appropriate amount of ethanol solution to dilute and mix evenly;

[0032] 2. Spray the aluminum plate (100*100) with the same batch and the same process to prepare a 5mm thick coating. Each 1mm is a unit layer. When there is no obvious sign of solvent, continue to prepare the next unit layer.

[0033] Comparative Example 2:

[0034] 1. Take 100g of silicone resin and heat it to 60°C, add 5g of zirconium boride into it, and stir thoroughly to obtain component A;

[0035] 2. Add an appropriate amount of ethanol solution to component A to dilute and mix evenly;

[0036] 3. Spray the aluminum plate (100*100) with the same batch and the same process to prepare a 5mm thick coating. Each 1mm is a unit layer. When there is no obvious sign of solvent, continue to prepare the next unit layer.

[0037] Comparative Example 3:

[0038] Compared with Example 1, 10 g of zirconium boride was added, and the rest was the same as Example 1.

[0039] Comparative Example 4:

[0040] Compared with Example 1, 15 g of zirconium boride was added, and the rest was the same as Example 1.

[0041] Table 1 Performance test data of products prepared in Comparative Examples 1-4

[0042]

[0043] Embodiment 1:

[0044] 1. Take 100g of silicone resin and heat it to 60°C, add 15g of zirconium boride into it, and stir thoroughly to obtain component A;

[0045] 2. Disperse 10g of ceramic microbeads in an appropriate amount of ethanol, add 1g of surface modifier, and mix well to obtain component B;

[0046] 3. Mix components A and B evenly to form final product D;

[0047] 4. Spray the aluminum plate (100*100) with the same batch and the same process that has been sandblasted to prepare a 5mm thick coating. Each 1mm is a unit layer. When there is no obvious sign of solvent, continue to prepare the next unit layer.

[0048] Embodiment 2:

[0049] 1. Take 100g of silicone resin and heat it to 60°C, add 15g of zirconium boride into it, and stir thoroughly to obtain component A;

[0050] 2. Disperse 20g of ceramic microbeads in an appropriate amount of ethanol, add 2g of surface modifier, and mix well to obtain component B;

[0051] 3. Mix components A and B evenly to form final product D;

[0052] 4. Spray the aluminum plate (100*100) with the same batch and the same process that has been sandblasted to prepare a 5mm thick coating. Each 1mm is a unit layer. When there is no obvious sign of solvent, continue to prepare the next unit layer.

[0053] Embodiment 3:

[0054] 1. Take 100g of silicone resin and heat it to 60°C, add 15g of zirconium boride into it, and stir thoroughly to obtain component A;

[0055] 2. Disperse 30g of ceramic microbeads in an appropriate amount of ethanol, add 3g of surface modifier, and mix well to obtain component B;

[0056] 3. Mix components A and B evenly to form final product D;

[0057] 4. Spray the aluminum plate (100*100) with the same batch and the same process that has been sandblasted to prepare a 5mm thick coating. Each 1mm is a unit layer. When there is no obvious sign of solvent, continue to prepare the next unit layer.

[0058] Embodiment 4:

[0059] 1. Take 100g of silicone resin and heat it to 60°C, add 15g of zirconium boride into it, and stir thoroughly to obtain component A;

[0060] 2. Disperse 30g of ceramic microbeads and 10g of chopped fibers in an appropriate amount of ethanol, add 4g of surface modifier, and mix well to obtain component B;

[0061] 3. Mix components A and B evenly to form final product D;

[0062] 4. Spray the aluminum plate (100*100) with the same batch and the same process that has been sandblasted to prepare a 5mm thick coating. Each 1mm is a unit layer. When there is no obvious sign of solvent, continue to prepare the next unit layer.

[0063] Embodiment 5:

[0064] 1. Take 100g of silicone resin and heat it to 60°C, add 15g of zirconium boride into it, and stir thoroughly to obtain component A;

[0065] 2. Disperse 30g of ceramic microbeads and 20g of chopped fibers in an appropriate amount of ethanol, add 6g of surface modifier, and mix well to obtain component B;

[0066] 3. Mix components A and B evenly to form final product D;

[0067] 4. Spray the aluminum plate (100*100) with the same batch and the same process that has been sandblasted to prepare a 5mm thick coating. Each 1mm is a unit layer. When there is no obvious sign of solvent, continue to prepare the next unit layer.

[0068] Embodiment 6:

[0069] 1. Take 100g of silicone resin and heat it to 60°C, add 15g of zirconium boride into it, and stir thoroughly to obtain component A;

[0070] 2. Disperse 30g of ceramic microbeads and 30g of chopped fibers in an appropriate amount of ethanol, add 6g of surface modifier, and mix well to obtain component B;

[0071] 3. Mix components A and B evenly to form final product D;

[0072] 4. Spray the aluminum plate (100*100) with the same batch and the same process that has been sandblasted to prepare a 5mm thick coating. Each 1mm is a unit layer. When there is no obvious sign of solvent, continue to prepare the next unit layer.

[0073] Table 2 Performance test data of products prepared in Examples 1-6

[0074]

[0075] Comparison of the test data in Table 2 and Table 1 shows that the addition of ceramic microbeads can significantly reduce the coating density and thermal conductivity and improve the emissivity, but has a certain impact on the hardness and line ablation rate; the addition of chopped fibers enhances the integrity of the coating, basically makes up for the defects of the microbeads, and improves the emissivity to a certain extent.

[0076] Embodiment 7:

[0077] 1. Take 100g of silicone resin and heat it to 60°C, add 15g of zirconium boride into it, and stir thoroughly to obtain component A;

[0078] 2. Disperse 30g of ceramic microbeads and 30g of chopped fibers in an appropriate amount of ethanol, add 6g of surface modifier, and mix well to obtain component B;

[0079] 3. Grind and stir 5g of lanthanum oxide and 5g of chromium oxide crystals in a ball mill. Sinter them in a crucible at high temperature after mixing them evenly. Cool them to room temperature with the furnace, add solvent and mix them evenly to form component C.

[0080] 4. After mixing components B and C, add component A and mix evenly to form the final product D;

[0081] 5. Spray the aluminum plate (100*100) with the same batch and the same process to prepare a 5mm thick coating. Each 1mm is a unit layer. When there is no obvious sign of solvent, continue to prepare the next unit layer.

[0082] Embodiment 8:

[0083] 1. Take 100g of silicone resin and heat it to 60°C, add 15g of zirconium boride into it, and stir thoroughly to obtain component A;

[0084] 2. Disperse 30g of ceramic microbeads and 30g of chopped fibers in an appropriate amount of ethanol, add 6g of surface modifier, and mix well to obtain component B;

[0085] 3. Put 10g of lanthanum oxide and 10g of chromium oxide crystals in a ball mill, grind and stir, mix evenly, place in a crucible for high temperature sintering, cool to room temperature with the furnace, add solvent and mix evenly to form component C;

[0086] 4. After mixing components B and C, add component A and mix evenly to form the final product D;

[0087] 5. Spray the aluminum plate (100*100) with the same batch and the same process to prepare a 5mm thick coating. Each 1mm is a unit layer. When there is no obvious sign of solvent, continue to prepare the next unit layer.

[0088] Embodiment 9:

[0089] 1. Take 100g of silicone resin and heat it to 60°C, add 15g of zirconium boride into it, and stir thoroughly to obtain component A;

[0090] 2. Disperse 30g of ceramic microbeads and 30g of chopped fibers in an appropriate amount of ethanol, add 6g of surface modifier, and mix well to obtain component B;

[0091] 3. Grind and stir 15g of lanthanum oxide and 15g of chromium oxide crystals in a ball mill. Sinter them in a crucible at high temperature after mixing them evenly. Cool them to room temperature with the furnace, add solvent and mix them evenly to form component C.

[0092] 4. After mixing components B and C, add component A and mix evenly to form the final product D;

[0093] 5. Spray the aluminum plate (100*100) with the same batch and the same process to prepare a 5mm thick coating. Each 1mm is a unit layer. When there is no obvious sign of solvent, continue to prepare the next unit layer.

[0094] Table 3 Performance test data of products prepared in Examples 7-9

[0095]

[0096] Comparison of the test data in Table 3 and Table 2 shows that lanthanum oxide and chromium oxide can further significantly improve the emissivity of the coating, reduce the linear ablation rate, have a certain effect on the hardness of the material, and have a negligible effect on the density and thermal conductivity of the material, which is a better preparation scheme.

[0097] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions of the technical solutions of the present invention made by ordinary technicians in the field should all be included in the protection scope of the present invention. The protection scope of the present invention shall be based on what is defined in the claims.

Claims

1. A method for preparing a thermal barrier coating, characterized in that: The following steps are involved: Add 5 to 15 parts by weight of a ceramic precursor to 100 parts by weight of an organic silicone resin, and mix thoroughly to obtain component A; 10 to 30 parts by weight of hollow microspheres and 10 to 30 parts by weight of chopped fibers are fully mixed and dispersed in solvent X, a surface modifier is added, and the mixture is uniformly mixed to form component B; Mix component A and component B evenly to form final product D; The final product D is sprayed or brushed on the material to be protected, and after the solvent evaporates and dries, an ablation-resistant thermal barrier coating is obtained.

2. The preparation method according to claim 1, characterized in that The organic silicon resin includes one of ladder polymethylsilsesquioxane, ladder polyphenylsilsesquioxane, trimethylmethoxysilane, methyltrimethoxysilane, methylphenyl silicone resin, phenyltrimethoxysilane, ethyl orthosilicate, and propyl orthosilicate.

3. The preparation method according to claim 1, characterized in that: Hollow microspheres include glass microspheres, ceramic microspheres or a mixture of the two, with a particle size of 50 to 100 um.

4. The preparation method according to claim 1, characterized in that: The chopped fibers include mixed fibers of one or more of high silica fibers, glass fibers, quartz fibers, aramid fibers, and aramid sulfone fibers, and the fiber length is 50 to 100 um.

5. The preparation method according to claim 1, characterized in that: The ceramic precursor includes one of zirconium boride, silicon carbide, boron nitride, silicon tetraboride and silicon hexaboride.

6. The preparation method according to claim 1, characterized in that: The surface modifier includes one of γ-aminopropyltriethoxysilane, γ-(methacryloyloxy)propyltrimethylsilane, γ-glycidyloxypropyltrimethoxysilane, vinyltriethoxysilane and vinyltrimethoxysilane; the added amount of the surface modifier is 5% to 10% of the mass of the ceramic precursor.

7. The preparation method according to claim 1, characterized in that: The following steps are also included: 5 to 15 parts by mass of lanthanum oxide and 5 to 15 parts by mass of chromium oxide crystals are put into a ball mill for grinding and stirring. After mixing evenly, they are placed in a crucible for high-temperature sintering, cooled to room temperature with the furnace, and solvent Y is added and mixed evenly to form component C; component C is added to the mixture of component A and component B to form the final product D.

8. The preparation method according to claim 7, characterized in that: The solvent X and the solvent Y are the same or different, are miscible with each other, and can dissolve the silicone resin, the ceramic precursor, lanthanum oxide, and chromium oxide.

9. The preparation method according to claim 8, characterized in that: The solvent X and the solvent Y include one of ethanol, isopropanol, toluene, n-hexane, chloroform, tetrachloromethane, and bromate solution.

10. A thermal barrier coating, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Heat-insulation ablation-resistant maintainable repairing agent and coating dual-purpose slurry, preparation method and application

    CN110819228A

  • Thermal protection coating and preparation method thereof

    CN112831747A